Spatial Analysis and Soil Biophysical Evaluation of Dryland Degradation in Pandansari Village, Warungasem Subdistrict, Batang Regency - Farchan Mushaf Al Ramadhani; Eka Adi Supriyanto; Muhammad Akmal Faza (Agroteknika, 2026)
Dryland is vulnerable to degradation due to intensive land use and inadequate conservation practices. This study aimed to analyze the potential and status of dryland degradation in Pandansari Village, Batang Regency, based on spatial analysis and soil biophysical parameters. A quantitative descriptive approach was employed through GIS-based spatial analysis, field surveys, and laboratory soil analysis. Land degradation potential and status were assessed according to Government Regulation Number 150 of 2000 and Minister of Environment Regulation Number 07 of 2006. Spatial analysis was conducted by overlaying soil type, slope, rainfall, and land use maps, resulting in three Land Mapping Units (LMUs). Field verification was performed at nine sampling points, with three sampling points representing each LMU. Soil degradation status was evaluated using ten parameters, namely solum thickness, surface rock fragments, soil fraction composition, bulk density, total porosity, permeability rate, soil pH, electrical conductivity, redox potential, and total soil microbial population. The results showed that land degradation potential in Pandansari Village was classified into low (70.53 ha), moderate (109.84 ha), and high (1.23 ha) categories. Field verification indicated that the Low and Moderate Soil Degradation Potential LMUs were classified as Slightly Degraded (R.I), whereas the High Soil Degradation Potential LMU was classified as Moderately Degraded (R.II). The main limiting factors were soil fraction composition, surface rock fragments, permeability rate, and redox conditions. Recommended conservation measures include organic matter application, mulching, cover crops, conservation tillage, revegetation, and mechanical conservation practices to maintain sustainable land productivity.